β-Boswellic Acid Suppresses Breast Precancerous Lesions via GLUT1 Targeting-Mediated Glycolysis Inhibition and AMPK Pathway Activation - Bie, Fengjie; Zhang, Guijuan; Yan, Xianxin; Ma, Xinyi; Zhan, Sha; Qiu, Yebei; Cao, Jingyu; Ma, Yi; Ma, Min (Frontiers in Oncology, 2022)
Breast carcinoma is a multistep progressive disease. Precancerous prevention seems to be crucial. β-Boswellic acid (β-BA), the main component of folk medicine Boswellia serrata (B. serrata), has been reported to be effective in various of disease including tumors. In this work, we demonstrated that β-Boswellic acid could inhibit the breast precancerous lesions in rat disease models. Consistently β-BA could suppress proliferation and induce apoptosis on MCF-10AT without significantly influence MCF-10A. KEGG analysis suggested β-BA may interfere with metabolic pathway. Metabolism-related assays presented that β-BA suppressed glycolysis and reduced ATP production, which then activated AMPK pathway and inhibited mTOR pathway to limit MCF-10AT proliferation. Further molecular docking analysis suggested that GLUT1 might be the target of β-BA. Forced expression of GLUT1 could rescue the glycolysis suppression and survival limitation induced by β-BA on MCF-10AT. Taken together, β-BA could relieve precancerous lesions in vivo and in vitro through GLUT1-targeting induced glycolysis suppression, and AMPK/mTOR pathway alterations. Here we offered a molecular basis for β-BA to develop as a promising drug candidate for breast precancerous prevention.